Successive Harvest in Brassica rapa ssp. nipposinica: Energy-efficient Phytonutrient and Biomass Production - Ethan W. Darby; Sarah P. Armstrong; Gioia D. Massa; Kellie J. Walters (Journal of the American Society for Horticultural Science)
Astronaut health and subsequent mission success depend on access to a full range of bioavailable vitamins, something lacking in the current space diet. As sustainable food production systems are developed for use during long space flights, the utilization of continuous harvest (cut-and-come-again) methods can play a role in efficient use of limited space and resources. However, it is unknown how successive harvests will affect the desired phytonutrient profile over time. This study was designed to determine the optimal indicator of harvest readiness (time vs. development) for peak phytonutrient production, and to determine the effect of five consecutive harvests on phytonutrient concentrations and biomass yield of Brassica rapa ssp. nipposinica ‘Red Hybrid’. Seeds were sown in a growth chamber and transplanted after 14 days into raft deep-water culture systems. A target air temperature of 23 °C and a CO2 concentration of 2800 μmol·mol−1 were set to emulate space-station conditions, and 200 or 800 μmol·m−2·s−1 of light were applied at a 16-h photoperiod. Nutrient solution was composed of a 12.0N–1.7P–13.3K complete fertilizer supplemented with MgSO4, and provided 100 or 200 mg·L−1 N during the propagation and raft production phases, respectively. After 10 days (time) or eight leaves produced (development), leaves that extended 3.5 cm above the substrate surface were harvested. Harvests were repeated cyclically to achieve five harvests per plant. This was conducted twice in time. Tissue morphology and phytonutrient concentration were evaluated. Harvest interval (time or development) was compared to determine optimal crop-cycle length and harvest methodology for consistent nutritious vegetable production.